PENGARUH ILLEGAL FISHING DI ZONA EKONOMI EKSKLUSIF TERHADAP PEREKONOMIAN DI KABUPATEN NATUNA - Okta Ontika Nugrah; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research  analyzes how the influence of Illegal Fishing in the Exclusive Economic Zone on the economy in Natua Regency. Illegal fishing activities in WPP-RI have resulted in huge losses for Indonesia, one of which is material losses caused by illegal fishing. In mid-2016, in March, May and June, three Chinese fishing boats were caught carrying out illegal fishing activities in the North Natuna Sea. The Joko widodo government made efforts which can be broadly classified into two approaches, namely the hard approach by strengthening the enforcement of maritime defense, security and safety to protect the territory and marine resources, and the soft approach by strengthening diplomacy. and maritime negotiations. These two efforts are to realize Indonesia as the world's maritime axis.This research uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles, websites. This study uses the perspective of Liberalism and the theory of Maritime Security. The results of this paper indicate that Material Losses are set based on the basic assumption. If MSY (Maximum Sustainable Yield = Maximum Sustainable Catch) of fish = 6.4 million tons / year, then what is lost is stolen and disposed of around 1.6 million tons / year . If the selling price of fish abroad is an average of 2 USD/kg, the annual loss can reach Rp. 30 trillion. Keywords: Illegal Fishing, Maritime Security, Chinese Fishermen.